A methodological approach to assess the ropy character of stirred acid dairy gels based on the measure of adhesiveness - Siwar Nahali; Audrey Gilbert; Charlotte Marchand; Marie-Hélène Lessard; Donna Miller; Sébastien Fraud; Steve Labrie; Sylvie L. Turgeon (JDS Communications)
This work aims to evaluate the potential and limits of adhesiveness measurement using a texturometer to assess the ropiness of acid dairy gels for starter selection. Commercial yogurts of various formulations and textures were used to assess the ability of adhesiveness to detect ropiness and to compare performance of different probes. Chemically acidified gels using different concentrations of glucono-delta-lactone (GDL) were tested to determine the effect of pH on adhesiveness. In addition, acidified (GDL) milk containing 3 exopolysaccharide-producing adjunct strains was produced to evaluate the detection of ropy strains using adhesiveness, compared with an inoculation loop stretching test. The adhesiveness of commercial yogurts was mainly affected by its formulation. Visually ropier commercial yogurts with high protein and fat contents presented higher adhesiveness. Globally, adhesiveness analysis was not affected by probe material, but larger probes resulted in higher adhesiveness values. The addition of adjuncts increased the adhesiveness of GDL gels compared with the controls. Results between inoculation loop stretching test and adhesiveness were similar, except for Lactobacillus delbrueckii lactis LMA-1511, which exhibited high adhesiveness but no threading with the loop stretching test. When varying GDL concentration, adhesiveness increased with decreasing pH until pH 4.45, and remained stable until pH 4.18. In the pH zone from 4.18 to 4.45, differences in adhesiveness could indicate the presence of a ropy strain. This method is promising for industries as a quality control or screening method for starter cultures due to its simplicity and the availability of texturometers.